Anthropometrical studies on greenlanders from two villages in the Upernavik area. - Balslev Jørgensen, J.; Dahl, Jens; Sangvichien, Sanjai (Meddelelser om Grønland, 1976)
The anthropometrical studies in Augpilagtoq and Kraulshavn, Upernavik Municipality, were carried out during two expeditions; in 1968 to Augpilagtoq and in 1969 to Kraulshavn. In 1968 the expedition included several human-biological aspects and was joined by scientists from the other Scandinavian countries. In 1969 the expedition included many biological aspects too, but this year all members were Danes. Both expeditions were financed by grants from Statens Lægevidenskabelige Forskningsråd (L 78/68 and 512-33/69). The ministry for Greenland granted free transportation for some of the members of the expeditions.